2011
DOI: 10.1007/s11837-011-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process variables on Mg-Si particles and extrudability of 6xxx series aluminum extrusions

Abstract: How would you……describe the overall significance of this paper? Process variables have significant impact on extrudability and product properties through their effects on the characteristics of Mg-Si particles in 6xxx series aluminum extrusions. This paper reviews the effects of MgSi particles on extrudability and the effects of major process parameters on the characteristics of Mg-Si particles as well as on the process and product properties of 6xxx series aluminum extrusions. This provides a framework for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…As a consequence, alloy K with a higher volume fraction and particle count of insoluble Mg 2 Si particles and AlFeSi intermetallics (Fig. 3) will be harder and more difficult to extrude and point to the need to reduce the extrusion speed significantly to avoid unsuitable surface quality (Zhu et al, 2011). Consequently, the volumetric energy, U , given by the area under the corresponding stress-strain curve, is greater for alloy K than it is for alloy B:…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, alloy K with a higher volume fraction and particle count of insoluble Mg 2 Si particles and AlFeSi intermetallics (Fig. 3) will be harder and more difficult to extrude and point to the need to reduce the extrusion speed significantly to avoid unsuitable surface quality (Zhu et al, 2011). Consequently, the volumetric energy, U , given by the area under the corresponding stress-strain curve, is greater for alloy K than it is for alloy B:…”
Section: Discussionmentioning
confidence: 99%
“…[2] This solute-rich liquid leads to the formation of the inter-dendritic secondary phases, such as Fe-rich intermetallic compounds (Fe-IMCs) and strengthening Mg 2 Si precipitates. [3,4] Previous studies show that a c -AlFeSi and b-AlFeSi are the two dominant Fe-IMCs in 6063 Al alloys. [5][6][7][8] 3D analysis of these Fe-IMCs after extraction from the primary a-Al using an Al dissolution approach revealed that a c -Al(FeMn)Si (from now referred to as a c -AlFeSi) had a dendritic-like morphology while b-AlFeSi had a plate-like morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The finer the precipitates, the greater their surface:volume ratio and the faster they dissolve [ 31 ]. The increase in the size or non-uniform distribution of coarse Mg 2 Si particles decreases the extrusion speed and the increase in solid solution of Mg and Si in the billet can cause a decrease in the maximum extrusion speed [ 32 ].…”
Section: Resultsmentioning
confidence: 99%